In Silico Investigation of Propolis Compounds as Potential Neuroprotective Agent (Biointerface Research in Applied Chemistry, 2022)
Alzheimer's disease is a neurodegenerative disorder caused by several factors, namely neuroinflammation, neuronal apoptosis, and low levels of neurotransmitter Acetylcholine. MAPK14, TNF-α, IL-1β, and NF-KB are proteins that are directly involved in the neuroinflammatory signaling pathway. Caspase3 is involved in neuronal apoptosis, and AChE act as a neurotransmitter breakdown catalyst. In this study, docking analysis of propolis compounds was successfully done against six proteins related neurodegenerative. The results show that 18 compounds of propolis have a better binding affinity than standard drugs (donepezil, huperzine A, fostamatinib, and amrinone). For AChE, only isoetin has a lower binding affinity than donepezil. Isoetin was also observed to inhibit the Caspase3, MAPK14, NF-kB, and TNF-α. In silico prediction of the blood-brain barrier (BBB) permeant revealed that three propolis compounds could pass the BBB, they are isoetin; 5,7,8,3′,4′-pentamethoxy flavone; and flavenochromane C. 5,7,8,3′,4′-pentamethoxy flavone can strongly bind to NF-kB and TNF-α, while Flavenochromane C potentially inhibits MAPK14, NF-kB, and TNF-α better than standard drugs. These compounds are firstly reported as neuroprotective agents. They can be further explored and could be used as a backbone molecule to develop a new treatment for neurodegenerative diseases.